Study on Variability in Field Experiments of Bhal and Coastal Zone Crops and Development Yardstick - Motaka, G. N.; Darji, V. B.; Parmar, D. J.; Kalola, A. D.; Vaishnav, P. R. (International Journal of Bio-resource and Stress Management, 2017)
The data on CV % for Bhal and coastal zone of Gujarat crops yield along with other details of 1117 field experiments conducted during 1989−90 to 2014−15 at Agriculture research station, Anand Agricultural University, Arnej and Dhandhuka center were collected and analyzed using BASIC proramme. Most of the experiments carried out in plant breeding discipline (837) among the 21% experiments had greater than 18% CV followed by Agronomy (170) among 24% experiments had greater than 18% CV. More than 88% experiments carried out in RBD and about 23% experiments of them have CV % higher than the fiducial limit. According to different treatment, Treatments group 6−10, 16−20, 21−25 and 26−30 showed lower CV % compared to overall average CV %. Plot size and shape also play an important role in the precision of the experiment results. Therefore, plot size of the experiments 3 to 9 m2 seems to be optimum plot size of bhal and coastal zone crops. All the experiments conducted in these regions had 2 to 6 replications. Out of them, most of experiments were conducted with 2 to 4 replications and Most of the experiments were conducted with 2, 3 and 4 replications. The experiments with 5 replications had high variability. The upper fiducial limits (the yardstick) of CV % at 95% confidence based on non-central ‘t’ distribution were worked out for accepting the results of Bhal and coastal zone crops experiments which emerged as 18%.